Molecular Subtypes Based on the Stemness Index Predict Prognosis in Glioma Patients - Tan, Jun; Zhu, Hecheng; Tang, Guihua; Liu, Hongwei; Wanggou, Siyi; Cao, Yudong; Xin, Zhaoqi; Zhou, Quanwei; Zhan, Chaohong; Wu, Zhaoping; Guo, Youwei; Jiang, Zhipeng; et al. (Frontiers in Genetics, 2021)
Glioma is the common histological subtype of malignancy in the central nervous system, with high morbidity and mortality. Glioma cancer stem cells (CSCs) play essential roles in tumor recurrence and treatment resistance. Thus, exploring the stem cell-related genes and subtypes in glioma is important. In this study, we collected the RNA-seq data and clinical information of glioma patients from The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA) databases. With the differentially expressed genes (DEGs) and weighted gene correlation network analyses (WGCNA), we identified 86 mRNAsi-related genes in 583 samples from TCGA RNA-seq dataset. Furthermore, these samples from TCGA database could be divided into two significantly different subtypes with different prognoses based on the mRNAsi corresponding gene, which could also be validated in the CGGA database. The clinical characteristics and immune cell infiltrate distribution of the two stemness subtypes are different. Then, functional enrichment analyses were performed to identify the different GO terms and pathways in the two different subtypes. Moreover, we constructed a stemness subtype-related risk score model and nomogram to predict the prognosis of glioma patients. Finally, we selected one gene (ETV2) from the risk score model for experimental validation. The results showed that ETV2 can contribute to the invasion, migration and EMT process of glioma. In conclusion, we identiﬁed two distinct molecular subtypes and potential therapeutic targets of glioma, which could provide new insights for the development of precision diagnosis and prognostic prediction for glioma patients.